2018
DOI: 10.5603/fm.a2017.0076
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography evaluation of ponticulus posticus in patients with cleft lip and palate: a retrospective radio-anatomic study

Abstract: Ponticulus posticus is an important anomaly and the presence of PP is important for patients. PP can have clinical significance in cervical spine surgery as this study has indicated that the likelihood of encountering PP is higher in patients with CLP. We suggest that PP should be taken into account prior to cervical vertebral surgery in patients with CLP. (Folia Morphol 2018; 77, 1: 72-78).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…PP is an important anomaly of the atlas vertebra [4,6,12]. It is associated with complications that have negative effects on the individual's quality of life, such as migraine without aura, headache, cervical pain, neck pain, shoulder pain, vertebra-basilar insufficiency, visual disorders, and speech and swallowing problems [3,4,6,8,9,12,16,24]. The importance of PP is not only because of its clinical effects, but is also related to the insertion of lateral mass screws in this area that is a common treatment for atlas fixation in cases of atlantoaxial instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PP is an important anomaly of the atlas vertebra [4,6,12]. It is associated with complications that have negative effects on the individual's quality of life, such as migraine without aura, headache, cervical pain, neck pain, shoulder pain, vertebra-basilar insufficiency, visual disorders, and speech and swallowing problems [3,4,6,8,9,12,16,24]. The importance of PP is not only because of its clinical effects, but is also related to the insertion of lateral mass screws in this area that is a common treatment for atlas fixation in cases of atlantoaxial instability.…”
Section: Discussionmentioning
confidence: 99%
“…In the Iranian population, the frequency of PP has been estimated at 20.6% [10]. PP may be associated with conditions, such as migraine without aura, headache, cervical pain, diplopia, neck pain, shoulder pain, hearing loss, vertebrobasilar insufficiency, visual disorders, speech and swallowing problems, and vertigo [3,4,5,6,8,9,16,21,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Leonardi et al ( 31 ) reached a converging conclusion in which 34.2% of patients with PDC showed PP as opposed to the group of normal population (20%) ( 34 ). Bayrakdar et al found that there was a significant association between PP and cleft lip ( 35 ). In this study, the incidence of PP in the cleft-palate group was 22.2% compared to 9% in normal group.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size was calculated using the PASS 11 software and with regard to the previous study conducted by Bayrakdar et al 5 It was found to be a minimum of 81 subjects in each group. Ethical approval for this study was obtained from the Ethics Committee of Tehran University of Medical Sciences (Code: IR.TUMS.DENTISTRY.REC.1398.124).…”
Section: Methodsmentioning
confidence: 99%